Variability in dissolved organic matter optical properties in surface waters in the Amerasian Basin - Guéguen, Céline; Itoh, Motoyo; Kikuchi, Takashi; Eert, Jane; Williams, William J. (Frontiers in Marine Science, 2015)
Surface absorption and fluorescence measurements of Dissolved Organic Matter (DOM) were conducted along with hydrographic parameters in the Canada and Makarov Basins. Parallel factor analysis of DOM fluorescence identified four humic-like and one protein-like component in all 107 surface samples. Based on strong negative trends observed between the spectral slope in the 275-295 nm range and absorption at 370 nm, and four humic-like components C1-C4, the DOM character was found to be basin-dependent. The Makarov basin surface DOM was largely dominated by high molecular weight and humic-rich material whereas the Canada Basin surface DOM was more heterogeneous with a marked influence of in situ production. This study highlights that absorbing and fluorescing measurements can be used successfully to trace and differentiate DOM from diverse sources and across frontal zones, and as such can be convenient and complementary tools for the better understanding of marine biogeochemical cycling of carbon.